Optical characterization of ZnO - Gaspar, C.
The green (2.19 eV) and yellow (2.2 eV)luminescence bands in ZnO polycrystalline samples were studied by PL, PLE, TRPL and lifetime measurements. A shift towards higher energies of the green emission band is observed for temperatures above 35 K.